Benthic and Demersal Scavenger Biodiversity in the Eastern End of the Clarion-Clipperton Zone – An Area Marked for Polymetallic Nodule Mining - Harbour, Rob P.; Leitner, Astrid B.; Ruehlemann, Carsten; Vink, Annemiek; Sweetman, Andrew K. (Frontiers in Marine Science, 2020)
In the Clarion-Clipperton Zone (CCZ) in the north-eastern Pacific Ocean ca. 30 billion tonnes of polymetallic nodules, rich in metals critical for frontier technologies, lay on the sediment surface over an area of 4 to 5 million square kilometres. For this reason, there is accelerating interest in deep-sea mineral mining in the CCZ. Few data exist concerning marine biodiversity in this enormous region and a solid understanding of baseline biodiversity and ecosystem function are necessary in order to inform effective management strategies, conservation and monitoring in the event that mining goes ahead in the CCZ. In this study, 10 in situ baited-camera experiments were carried out in the BGR (The Federal Institute for Geosciences and Natural Resources, Germany) license area in the eastern CCZ to document the biodiversity of scavengers and their feeding activities. Twelve different bait-attending taxa were identified. The most common of these were macrourid, ophidiid and zoarcid fishes, and dendrobranchiate shrimp. Successional patterns regarding their time of arrival were also observed. The bait consumption rate was measured, and a mean scavenging rate of 878 g d-1 ± 113 (SE, n = 9) was calculated, with the rattail Coryphaenoides spp. responsible for the majority of the bait consumption. Polymetallic nodule size did not significantly affect community structure, diversity or scavenging rates within the BGR license area, but significant differences were found in community structure between the BGR area and other areas of the eastern CCZ (the Ocean Minerals of Singapore and UK1 areas). This study increases our knowledge of deep-sea scavenging communities in an area targeted for deep-sea mining.